Benign inflammatory myofibroblastic tumour of the nose: a rare case report - Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Ramachandran, Manimaran; Natarajan, Praveen Ganesh; Rajamanohar, Vimal Chander (International Surgery Journal, 2019)
Inflammatory myofibroblastic tumor (IMT) of the head and neck region are rare and benign and of unknown etiology. They mimic as malignant lesions both clinically and radiologically. It encompasses a spectrum of myofibroblastic proliferation along with varying amount of inflammatory infiltrate. Recently, the concept of this lesion being reactive has been challenged based on the clinical demonstration of recurrences and metastasis and cytogenetic evidence of acquired clonal chromosomal abnormalities. Here we report a case of a 16 year old male who presented with a swelling on the nasal dorsum for 6 months. MRI and FNAC revealed a spindle cell neoplasm. The swelling was resected completely under general anaesthesia. Histopathology with immunohistochemistry proved it to be a benign inflammatory myofibrobalstic tumour. Complete surgical resection is the best treatment modality for IMT.